Civil Liability of Medical Personnel for Malpractice in Digital Health Services ( Telemedicine ): Analysis of Health Law and Civil Law - Kesuma, Ronny Chen Indra Nata; Khayatudin , Khayatudin; Hasibuan , Ali Huristak Hartawan (Academia Open, 2026)
General Background: Telemedicine has expanded digital healthcare access and transformed healthcare delivery through information technology. Specific Background: Despite improving efficiency and healthcare accessibility, telemedicine creates legal issues related to medical malpractice, patient protection, and civil liability. Knowledge Gap: Indonesian health regulations recognize telemedicine but do not comprehensively regulate civil liability for malpractice in digital healthcare services. Aims: This study analyzes the civil liability of medical personnel in telemedicine from health law and civil law perspectives. Results: The study finds that telemedicine remains subject to professional standards, patient safety, and medical ethics. The legal relationship between medical personnel and patients is classified as an inspanning verbintenis, requiring maximum professional effort rather than guaranteed outcomes. Civil liability may arise through breach of contract or unlawful acts, while healthcare facilities and digital platforms may also bear institutional responsibility. Novelty: This study integrates health law and civil law approaches in constructing telemedicine malpractice liability. Implications: Stronger telemedicine regulations, operational standards, and electronic evidence mechanisms are necessary to ensure legal certainty and patient protection in digital healthcare services. Highlights: Therapeutic agreements in remote medical services are classified as obligations of maximum professional effort. Patient claims may be pursued through contractual breaches or unlawful conduct provisions. Digital healthcare platforms and healthcare facilities may bear institutional responsibility for system-related losses. Keywords :Telemedicine , Medical Malpractice , Civil Liability